Analysis on available production resources in the cropland system of agro-pastoral integration - GUAN Fachun; BIAN Buyun; HUANG Lihua; ZHANG Yongfeng; LI Xiaohui; ZHANG Lichun (浙江大学学报. 农业与生命科学版, 2019)
In order to clarify the production potential of cropland ecosystems and the characteristics of available production resources under an agro-pastoral integration mode, field experiments were conducted by the contrast method. The results showed that: 1) Under a raising geese in a cornfield (RGICF) treatment, the weed total density was 1.41 times of CK, and the aboveground biomass of weeds was 1.68 times of CK at pre-grazing. At post-grazing, the weed total density and aboveground biomass reduced under the RGICF and CK treatments, but the decrease under the RGICF was greater than that of CK, indicating that agro-pastoral integration could increase the productivity of weed communities in the system. 2) During the entire grazing period, the weed biodiversity with the treatment of RGICF was higher than that of CK, indicating that the high biodiversity was maintained under the production mode of agro-pastoral integration. 3) The overall growth condition of maize plants with the treatment of RGICF was lower than that of the CK, and the maize resource quantities were reduced by 8.22% compared with the CK, but all the net yield with the treatment of RGICF was significantly higher than that of the CK, because the earnings by raising geese were enough to compensate for the loss of maize production. Moreover, the total of 4 836.75 kg/hm2 organic fertilizer was also produced to return to the field under the RGICF treatment. In a word, more available resources are produced under the mode of agropastoral integration mode, which lays a foundation for improving cropland productivity and doubling production efficiency on the basis of maintaining the high biodiversity.